Impact of Energy Efficient Design Strategies on Users Comfort in Selected Mixed-Use Buildings in Lagos State, Nigeria. Issue 1 (1st September 2022) - Sholanke, A. B.; Alugah, K. D. T.; Ademo, J. A.; Adisa, O. S.
Abstract: Human comfort is a major criterion for mixed-use buildings to be habitable, leading to the usage of technologies such as HVAC and artificial lighting. These devices demand high electricity, causing a 25% rise in building greenhouse gas emissions. It is important for architects to develop energy efficient design strategies in order to maintain and improve user comfort in mixed-use buildings. This study investigated the impact of energy efficiency design strategies on users' comfort in selected mixed-used building in Lagos State, Nigeria, with a view to identify areas for further improvements. The research adopted a quantitative approach. A structured questionnaire was used to obtain data. The Statistical Product & Service Solutions software was used to analyse the data. The result was presented with the aid of texts, tables and graphs. The findings indicated that building orientation was one of the most important techniques, affecting each dimension of human comfort. This revelation suggests that when adopting energy efficiency measures, a building's early design stage should focus on enhancing human comfort. The study recommended that professionals conduct critical analysis on buildings in the design stage to guarantee energy-efficient approaches used throughout the planning, design, and construction stages of mixed-use buildings. In order to create sustainable future designs, it is therefore necessary to recognise the significance of energy efficient design techniques on users' comfort.